Clinical Anatomy of the Front Face. Topography of the Oral Cavity - Tastanova Gulchexra Eshtayevna; Tulemetov Sabrjan Kalikovich; Nabiyeva Jumagul Baxtiyorovna (Zien Journals, 2023)
The front of the face is a complex region with different structures that contribute to the aesthetics and functionality of the face. Understanding the Clinical Anatomy of this region is very important for medical professionals, in particular dentists and oral surgeons, as they often face such conditions and perform operations in the oral cavity. This article focuses on the topography of the oral cavity to provide an overview of the Clinical Anatomy of the frontal area of the face.
Keywords: face area; cheek; forehead; muscles